2000
DOI: 10.1080/00039890009603405
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Trichloroethylene in Drinking Water and Birth-Weight Outcomes

Abstract: An ecological epidemiological study was conducted with data obtained from an environmental dose-reconstruction study and the Arizona Birth Information Tapes. Before 1981, a portion of the city of Tucson water-distribution system was contaminated with trichloroethylene (i.e., < 5 micrograms per liter of water to 107 micrograms per liter of water). Target and comparison populations were selected with a Geographic Information System. Logistical-regression analysis revealed an association between maternal exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 5 publications
1
23
1
Order By: Relevance
“…From information provided in the article, we calculated unadjusted odds ratios for very low birth weight during the exposure and postexposure periods. For the exposure period, an unadjusted odds ratio of 2.61 was obtained, somewhat lower than the adjusted Full-term LBW unexposed births GIS modeling of groundwater plume (post-exposure) (7) Results set in bold type indicate those that were calculated by the reviewing authors. Abbreviations: LBW, low birth weight; MBWD, mean birth weight difference; VLBW, very low birth weight.…”
Section: Solventsmentioning
confidence: 99%
See 4 more Smart Citations
“…From information provided in the article, we calculated unadjusted odds ratios for very low birth weight during the exposure and postexposure periods. For the exposure period, an unadjusted odds ratio of 2.61 was obtained, somewhat lower than the adjusted Full-term LBW unexposed births GIS modeling of groundwater plume (post-exposure) (7) Results set in bold type indicate those that were calculated by the reviewing authors. Abbreviations: LBW, low birth weight; MBWD, mean birth weight difference; VLBW, very low birth weight.…”
Section: Solventsmentioning
confidence: 99%
“…The Massachusetts study (32) found an association between stillbirths and chlorinated surface water when compared with chloraminated surface water. Table 5 summarizes the characteristics and results of the five studies of chlorinated solvents and adverse birth outcomes (7,8,20,39,40). Three studies focused primarily on trichloroethylene (TCE) contamination in drinking water.…”
Section: Reviews 2002 • Bove Et Almentioning
confidence: 99%
See 3 more Smart Citations